Workshop dan Pendampingan Pembuatan Serta Penggunaan Media Realia Termodifikasi di MI Plus Al Falah Banjarmasin - J, Jumiati; A, Abdurrahim; Putra, Defin Shahrial; Arifa, Tutus Rani; Kumala, Sari; Fatrah, Siti (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Modified realia media is education that combines the real world into the digital, involving students in exploring lesson concepts with a direct touch from digital technology or augmented reality (AR). With advances in technology, teachers have become a real media learning experience that is not only interactive and visual, but also offers a challenging depth of knowledge for students. Modified realia media bridges students not only by presenting views, but rather opens the door for students to touch, explore and interact directly with the essence of lesson concepts. Through collaboration in workshops and mentoring, it is hoped that teachers will enrich their skills in using modified realia media, enabling them to create unforgettable learning experiences for every student they guide. This process involves a series of steps starting from needs analysis with questionnaires, in-depth face-to-face learning, detailed training, to comprehensive evaluation, forming the basis for increasing teacher knowledge and developing skills in integrating technology in teaching. The results show their ability to create media that is not only interesting, but also in line with the essence of learning. The creativity of teachers is visible in their teaching, enabling them to incorporate this technology into various dimensions of learning, opening and expanding horizons for students' understanding.